Bilateral muscle compensation occurs with a unilateral rotator cuff tear: A modeling study - Zoe M. Moore; Joshua Pataky; Meghan E. Vidt (PLoS ONE, 2025)
Bimanual tasks are necessary for daily activities but become difficult to complete with a musculoskeletal disorder. Rotator cuff tears (RCT) are a common musculoskeletal disorder. It is unclear how an unaffected contralateral limb compensates when performing bimanual tasks. This work used a computational model to examine the effects of a unilateral RCT on performance of loaded bimanual tasks. A bilateral upper limb model was developed in OpenSim (v3.3), then modified to represent 4 RCT severities ranging from no RCT to massive RCT. A shared load (13.3 N or 44.5 N) was added to the models to represent holding typical household and occupational objects. Three motions were used as inputs to the Computed Muscle Control algorithm: static postures at low and high arm positions, and a dynamic forward reach task. The point analysis tool was used to track the shared load position. Outcomes included muscle force normalized by peak isometric force and maximum hand position deviation relative to input kinematics. Quantitative trends were analyzed for each outcome. During static tasks, uninjured muscles on the injured side increased force contribution with increased external load and RCT severity. For the dynamic task, infraspinatus muscle force increased with the massive RCT severity on the unaffected side by 76% for the 13.3 N load and 91% for the 44.5 N load, indicating contralateral muscle compensation. Minimal deviation occurred for the position of the shared load during the low posture static and dynamic tasks. For the high posture static task there was an inferior (342 mm) position change toward the unaffected side (83 mm) with the massive RCT, 44.5 N load. The bilateral model developed here has provided insights into bilateral compensation with a unilateral RCT. This modeling tool can be used to enhance understanding of task performance in the context of rehabilitation.